2017
DOI: 10.19045/bspab.2017.600101
|View full text |Cite
|
Sign up to set email alerts
|

Yield and yield attributes of maize (Zea mays L.) as affected by detasseling and potassium fertilization

Abstract: Maize yield is low due to inadequate use of fertilizers and management practices in Pakistan. A field trial was carried out on potassium application and detassleing at Agronomy Research Farm, The University of Agriculture Peshawar, in 2015. The objectives were to find out the effect of six potassium levels (0, 25, 50, 75, 100 and 125 kg ha -1 ) and three detasseling stages (Tassel not removed, Detasseling at complete pollen shedding stage and Detasseling at complete post dried silking stage) on maize yielding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…Moreover, these findings are consistent with past studies that have reported the positive impact of P application and crop residue on the yield and quality of seed in maize [58][59][60]. Refs.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, these findings are consistent with past studies that have reported the positive impact of P application and crop residue on the yield and quality of seed in maize [58][59][60]. Refs.…”
Section: Discussionsupporting
confidence: 92%